Computational Identification of miRNAs and Temperature-Responsive lncRNAs From Mango (Mangifera indica L.) - Moh, Nann Miky Moh; Zhang, Peijing; Chen, Yujie; Chen, Ming (Frontiers in Genetics, 2021)
Mango is a major tropical fruit in the world and is known as the king of fruits because of its flavor, aroma, taste, and nutritional values. Although various regulatory roles of microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) have been investigated in many plants, there is yet an absence of such study in mango. This is the first study to provide information on non-coding RNAs (ncRNAs) of mango with the aims of identifying miRNAs and lncRNAs and discovering their potential functions by interaction prediction of the miRNAs, lncRNAs, and their target genes. In this analysis, about a hundred miRNAs and over 7,000 temperature-responsive lncRNAs were identified and the target genes of these ncRNAs were characterized. According to these results, the newly identified mango ncRNAs, like other plant ncRNAs, have a potential role in biological and metabolic pathways including plant growth and developmental process, pathogen defense mechanism, and stress-responsive process. Moreover, mango lncRNAs can target miRNAs to reduce the stability of lncRNAs and can function as molecular decoys or sponges of miRNAs. This paper would provide information about miRNAs and lncRNAs of mango and would help for further investigation of the specific functions of mango ncRNAs through wet lab experiments.